Unusual site for metastatic renal cell carcinoma – A case report - Fejsa Levakov, Aleksandra; Amidžić, Jelena; Ilić Sabo, Jelena; Lakić, Tanja; Vojinov, Saša; Grbić, Dragan (Vojnosanitetski pregled, 2021)
Introduction. The most common malignant tumor of the kidney is renal cell carcinoma (> 90%). The metastasis of the renal cell carcinoma in lingual base is very rare. Case report. Patient, 74 years old, renal cell carcinoma underwent radical nephrectomy with evacuation of regional lymph nodes and without any further therapy. After two years of disease-free period, patient appeared with the symptom of difficult swallowing. Ultrasound showed tumor spreading in number of organs. Histopathological analysis of tissue from lingual base confirmed metastatic tumor. Conclusion. After radical surgical treatment of the malignant disease, it is important to examine multiple organ systems. Appropriate approach to the diagnostics and evaluation the entire condition of the patient in this stage of the disease, especially lingual base can relieve patients discomfort and provide prolonged survival, even if the prognosis is unfavourable.